Type 2 diabetes and leucocyte DNA methylation: an epigenome-wide association study in over 1,500 older adults - Florath, Ines; Butterbach, K.; Heiss, J.; Bewerunge-Hudler, M.; Zhang, Y.; Schöttker, B.; Brenner, H. (2016)
Aims/hypothesis: Development of type 2 diabetes depends on environmental and genetic factors. We investigated the epigenome-wide association of prevalent diabetes with DNA methylation (DNAm) in peripheral blood. Methods: DNAm was measured in whole blood with the Illumina Infinium HumanMethylation450 BeadChip in two subsamples of participants from the ESTHER cohort study. Cohort 1 included 988 participants, who were consecutively recruited between July and October 2000 and cohort 2 included 527 randomly selected participants. The association of DNAm with prevalent type 2 diabetes at recruitment was estimated using median regression analysis adjusting for sex, age, BMI, smoking behaviour, cell composition and batch at 361,922 CpG sites. Results: Type 2 diabetes was prevalent in 16% of the participants, and diabetes was poorly controlled in 45% of the diabetic patients. In cohort 1 (discovery) DNAm at 39 CpGs was significantly associated with prevalent diabetes after correction for multiple testing. In cohort 2 (replication) at one of these CpGs, DNAm was still significantly associated. Decreasing methylation levels at cg19693031 with increasing fasting glucose and HbA1c concentrations were observed using restricted cubic spline analysis. In diabetic patients with poorly controlled diabetes, the decrease in estimated DNAm levels was approximately 5% in comparison with participants free of diagnosed diabetes. Conclusions/interpretation: Cg19693031, which is located within the 3'-untranslated region of TXNIP, might play a role in the pathophysiology of type 2 diabetes. This result appears biologically plausible given that thioredoxin-interacting protein is overexpressed in diabetic animals and humans and 3'-untranslated regions are known to play a regulatory role in gene expression.